Air Quality Analysis of Nitrogen Dioxide and Ozone (NO2 and O3) In The Chemistry Laboratory of Universitas Pakuan Bogor - Pekerti, Unggul Tri; Widyatama, Awang; Imawati, Naufa Dea; Syahputri, Yulian (Universitas Pakuan, 2023)
Universitas Pakuan is one of the universities in Bogor which has a chemistry education laboratory for practical purposes. In this study, the room tested is the instrument room and preparation room. Air testing of this work environment refers to the Minister of Manpower Regulation No. 05 of 2018. The test results for the instrument room and preparation room found that the levels of nitrogen dioxide (NO2) and ozone (O3) in the two rooms do not show any indication of NO2 and O3 pollution with result values below the detection limit testing (0.0066 ppm and 0.0491 ppm).